A Study On Fuzzy Alpha - Ext Sober Spaces - B. Amudhambigai; V. Madhuri (Zenodo, 2017)
In this paper, the new concept of Fuzzy -Exterior Sober Space (briefly, F -Ext Sober Space) is introduced. Two extension theorems for Fuzzy -Ext Sober Space are studied using fuzzy quasi-homeomorphism. In this connection, some equivalent statements for fuzzy -Ext Sober Spaces are also established. : {"references": ["1.\tChang.C.L., Fuzzy Topological Sapecs, Journal of Mathematical Analysis and Applications, 24, 182 - 190 (1968). 2.\tGierz G., Hofmann K.H., Keimel K., Lawson J.D., Mislove M. and Scott D.S., Continuous Lattices and Domains, Cambride University, Press, 2003. 3.\tKarim Belaid, Othman Echi and Sami Lazaar, T(\u03b1,\u03b2) - Spaces and the Wallman Compactification, IJMMS, 2004:68, 3717 - 3735. 4.\tLuoshan Xu, Continuous of Posets via Scott topology and Sobrification, Topology and its Applications, 153 (2006): 1886-1894. 5.\tLuoshan Xu and Zhenyan Yuan, Decomposition Properties of Sober Topologies on the Same Sets, Int. J. Contemp. Math. Sciences, Vol. 4, 2009, no. 28, 1397 - 1403. 6.\tOthman Echi, Quasi-Homeomorphism, Goldspectral Spaces and Jacspectral Spaces, Bollettino U. M. I (8) 6-B (2003), 489-507. 7.\tPalaniappan N., Fuzzy Topology, Alpha Science International, Pangbourne England. 8.\tWesley Kotze, Quasi-coincidence and Quasi-fuzzy Hausdorff, Journal of Mathematical Analysis and Applications, 116, 465-472 (1986). 9.\tZadeh L. A., Fuzzy Sets, Information and Control, 8 (1965), 338-353."]}